Experimental results of a Raspberry Pi and OLSR based wireless content centric network testbed: comparison of different platforms. (2017) - Barolli, Admir; Elmazi, Donald; Obukata, Ryoichiro; Oda, Tetsuya; Ikeda, Makoto; Barolli, Leonard
The Content Centric Networks (CCN) replaces the IP narrow waist of the internet architecture by a content layer. When a node wants to access a piece of content, it sends an Interest packet to the network. Then, the network by using the name of the content for routing forwards the Interest to one or more copies of the content object. In this paper, we present the implementation of a testbed for CCN. We analyse the performance of Optimised Link State Routing (OLSR) protocol in an indoor scenario. For evaluation, we considered delay and jitter metrics. The experimental results show that the nodes in the testbed were communicating smoothly and we got low values of delay and jitter.